MDA5-positive dermatomyositis without muscle weakness and rash: a case report and literature review - Xiao, Ping-Ping; Fan, Wei; Chen, Xu-Yan; Li, Ke-Cong; Li, Ting-Ting; Dong, Zhi-Gao (Frontiers in Medicine, 2024)
Melanoma differentiation-associated gene 5 (MDA5)-positive dermatomyositis (DM) is a rare systemic autoimmune disease associated with a high rate of mortality attributable to rapidly progressive interstitial lung disease. MDA5-positive DM is often complicated by a typical rash and muscle weakness. Herein, we describe a 50-year-old woman who presented with worsening pulmonary symptoms with an absence of typical clinical characteristics. We also review the treatments and prognosis made in similar cases, highlighting that closer attention should be paid to patients presenting with atypical DM, particularly when clinical manifestations such as rash and muscle weakness are not apparent.